(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To identify some factors associated with stress disorders in outpatients with migraine headaches. Research methods: A prospective, cross-sectional descriptive study conducted at the Neurology Clinic, Military Hospital 103, from April 2024 to April 2025. A total of 182 patients were interviewed using a standardized questionnaire, and stress disorder was assessed using the DASS 21 scale. Results: 115 patients (63.2%) had stress disorder (DASS 21 ≥ 15), mainly at mild and moderate levels. Differences in stress disorder among patient groups by pain intensity, attack duration, and frequency were statistically significant (p ≤ 0.001). Stress disorder differed significantly between groups with sleep disorders, anxiety disorders, depressive disorders, and those without each disorders (p < 0.05). However, only attack frequency (p = 0.022; OR = 2.3) and anxiety disorder (p = 0.002; OR = 4.1) showed moderate to strong associations with stress disorder. Epidemiological factors were not related to stress disorder. Conclusion: Almost two-thirds of migraine patients experienced stress disorder, highlighting its severity among migraine patients. The factors associated with stress disorder in migraine patients were attack frequency and anxiety disorder status.